2016
DOI: 10.2308/jmar-51392
|View full text |Cite
|
Sign up to set email alerts
|

Investor Reactions to Company Disclosure of High CEO Pay and High CEO-to-Employee Pay Ratio: An Experimental Investigation

Abstract: There is significant debate about the usefulness of disclosing the CEO-to-median employee pay ratio, as required under Section 953(b) of the Dodd-Frank Act in the United States. Using an experiment, we find that disclosing higher-than-industry CEO pay (versus comparable-to-industry CEO pay) marginally decreases perceived CEO pay fairness and perceived workplace climate, which is counteracted by a significant positive effect on perceived CEO attraction/retention ability, although there are no significant indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Specifically, as of 2017, Section 953(b) of the Dodd‐Frank Act requires disclosure of median employee pay and its ratio to CEO pay, thereby opening up the possibility to relate executive compensation to estimated inputs of employees and executives. An experiment by Kelly and Seow () suggests that distributive justice aspects of compensation disclosure can negatively affect participants’ judgements of CEO pay fairness and perceived workplace climate but simultaneously increase the expected ability to attract and retain CEO talent.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, as of 2017, Section 953(b) of the Dodd‐Frank Act requires disclosure of median employee pay and its ratio to CEO pay, thereby opening up the possibility to relate executive compensation to estimated inputs of employees and executives. An experiment by Kelly and Seow () suggests that distributive justice aspects of compensation disclosure can negatively affect participants’ judgements of CEO pay fairness and perceived workplace climate but simultaneously increase the expected ability to attract and retain CEO talent.…”
Section: Introductionmentioning
confidence: 99%
“…They declared that by the time shareholders are eager to sell their shares, they trigger short-term motivations in directors to maximize current share values. Kelly & Seow (2016) investigated the pays to CEOs in comparison with the industries' median. They demonstrated that too high disclosure in industries cause marginally reductions in the understanding of rewards' fairness.…”
Section: Transparency and Quality Of Financial Informationmentioning
confidence: 99%
“…Advocates of the DFA pay-equity disclosure contend that the increased transparency of CEO pay will improve companies’ accountability to their stakeholders (Adut et al , 2013), curtail excessive executive pay relative to their performance (Djankov et al , 2008) and provide public pressure to reduce excessive executive salaries (Mas, 2014). Others believe that the increased transparency of CEO pay dispersion[1] may have negative consequences such as increasing the perceived unfairness of compensation among employees (Kelly and Seow, 2016, 2018), which has been associated with low employee morale (Hamilton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, existing research has focused primarily on the effects of the DFA CEO compensation disclosure requirement from the investor perceptive (Kelly and Seow, 2016, 2018), while the possible impact of the disclosure on employee behavior remains unexamined. Regulators should consider how the increased availability of CEO pay-equity information may impact the behavior of all stakeholders, including employees when weighing the benefits against the costs of the DFA.…”
Section: Introductionmentioning
confidence: 99%